Pengaruh Metode Penilaian Persediaan Terhadap Tingkat Laba Perusahaan Pada PT. Ramayana Lestari Sentosa, Tbk - Hasibuan, David H.M. (Jurnal Ilmiah Ranggagading (JIR), 2010)
This research goal is to find out the registration of merchandise stock applied at PT Ramayana Lestari Sentosa, Tbk., how to prepare the merchandise stock and how about its influence towards profit degree of the company. The result of this research shows that the registration system of merchandise stock applied at PT Ramayana Lestari Sentosa, Tbk made use of perpetual registration and evaluation method by using LIFO method where the final merchandise was evaluated based on buying price determined previously. The influence of the evaluation method towards profit degree could make the profit decreases and then the tax obligation decreases as well. Keywords: the registration system of merchandise stock;